Compound Sentence Patterns in the Novel Left Handed Girl by Ayunda Nisa Chaira - Hilmayanti Pando; Usman Usman; Hajrah Hajrah (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract.This study aims to describe the pattern of compound sentences in the novel Left Handed Girl by Ayunda Nisa Chaira. This type of research is descriptive qualitative research. The data collection technique used is the listening and note-taking technique. The data analysis technique used is to process, analyze, and present data objectively to obtain data in research. The results of this study are twofold, the first, namely compound equivalent sentences consisting of parallel equivalent compound sentences consisting of the SP/PPel pattern, the SPpel/PPel pattern, the SPPel/SPPel pattern, the SPOK/PO pattern, the SPK/PO pattern, the SP pattern. /SPPel, SPOK/PPel pattern, SPKPel/SPO pattern, POK/PPel pattern, SPKPel/PPelO pattern, PPelKPel/SPOPel pattern, PPelK/PKO pattern, SPpelO/SPPel pattern, SPPel/SPpelO pattern, SPKPel/SPOPel pattern, and pattern SPO/POPel, and opposite equivalent compound sentence patterns, consisting of SPPel/PPel patterns and PSPPelO/SPPel patterns, and the second, multilevel compound sentence patterns consisting of, SPPel/PO patterns, SPPel/PPel patterns, SPO/SPel patterns, SPPelK/SPPel pattern, SPPel/PelSPO pattern, SPPel/SPPel pattern, SPPel/SPOK pattern, SP/SPPel pattern, SPK/SPPel pattern, SPPel/PK pattern, SPO/SPO pattern, SPKPel/PSPK pattern, SPKPel/SPPelKPel pattern, PSPelK/SPOKO pattern, SPOPel/SPPel pattern, SPPel/SPO pattern, SPPel/SP pattern, and SPOKPel/SPO pattern. Keywords: Compound Sentence Patterns, Novel, Left Handed Girl